منحنى فيليبس الكينزي الجديد دراسة قياسية لعينة من الدول العربية خلال الفترة 1991-2018 - جوادي, عصام (جامعة الوادي - university of eloued, 2020)
إن الهدف من هذه الدراسة هو تفسير ديناميكية التضخم في عينة من الدول العربية خلال الفترة 1991- 2018 حيث قمنا بتقدير منحنى فيليبس الأصلي، المدعم بالتوقعات المتكيفة ومنحنى فيليبس الكينزي الجديد باستعمال أدوات القياس الاقتصادي لبيانات البانيل حيث توصلنا إلى أن منحنى فيليبس الكينزي الجديد قادر على تفسير ديناميكية التضخم في الدول العربية إنطلاقا من سلامة النموذج المقدر من الناحية الإحصائية والاقتصادية، كما أكدت النماذج التقليدية عدم وجود علاقة بين البطالة والتضخم في الدول العربية في الأجل الطويل بسبب ضعف معامل التحديد وغياب معنوية المعالم The objective of this paper is to study the dynamic of inflation in a sample of Arab countries during the period 1991-2018, we estimated the original Phillips curve, Phillips curve with adaptive expectations and The new Keynesian Phillips curve, using econometrics instruments of Panel data, we found that The new Keynesian Phillips curve able to explain the dynamics of inflation in the Arab countries, the traditional models confirmed: there is no relationship between unemployment and inflation in Arab countries in the long run because of the weakness of the coefficient of determination and the parameters are not significant.
The new Philips Keynesian curve Econometric study for a sample of Arab countries during the period 1991-2018
مقال
Keywords: منحنى فيليبس الكينزي الجديد ; التوقعات العقلانية ; التوقعات المتكيفة ; نموذج كالفو ; طريقة العزوم المعممة; The new Keynesian Phillips curve, rational expectations, adaptive expectations, Calvo model, generalized method of moments